Heavy Study Investment in Italian College Students. An Analysis of Loscalzo and Giannini’s (2017) Studyholism Comprehensive Model - Loscalzo, Yura; Giannini, Marco (Frontiers in Psychiatry, 2019)
Loscalzo and Giannini (2017) recently proposed the construct of Studyholism (or obsession toward study) and a theoretical model highlighting its potential antecedents and outcomes. This study aims to analyze some of these antecedents and outcomes by means of a path analysis including both Studyholism and Study Engagement. The participants are 1958 Italian college students aged between 18 and 60 years (M age = 23.53±4.43) and heterogeneous as far as concern their year and major of study, as well as concerning the city in which they attended their courses. They filled some instruments that allow evaluating Studyholism and Study Engagement, along with individual and situational antecedents (e.g., worry, overstudy climate) and outcomes (e.g., sleep quality, study-relationships conflict, dropout intention). In addition to the path model we performed aiming to test the direct effects we hypothesized, we performed two MANOVAs for analyzing if there were differences on the antecedents and outcomes among the four kinds of student suggested by Loscalzo and Giannini (2017; i.e., Engaged Studyholics, Disengaged Studyholics, Engaged students, Detached students). The results of this study support Loscalzo and Giannini (2017) conceptualization of Studyholism as an internalizing disorder since worry is the strongest predictor of Studyholism (β = .67, p < .001). In addition, in line with Loscalzo and Giannini’s (2017) theorization, we found some differences among the four kinds of students on both the antecedents and outcomes we analyzed. This study has critical theoretical, preventive, and clinical implications. It supports the definition of Studyholism as an OCD-related disorder. Also, about preventive implications, it shows that interventions aiming to favor students’ wellbeing should target also engaged students, since Study Engagement predicts social impairment as well as to Studyholism. Finally, it suggest that in a clinical setting it is important to distinguish between Disengaged Studyholics and Engaged Studyholics as they have different relationships with some antecedents and outcomes; also, they both have functional impairment, even if in different areas.